A case of upper lip necrosis after cosmetic injection of hyaluronic acid soft‐tissue filler—Does capillary infarction play a role in the development of vascular compromise, and what are the implications?. (8th April 2020) - Hirsch, Peter; Infanger, Manfred; Kraus, Armin
Abstract: Facial rejuvenation with injectable filler substances is a frequently applied outpatient procedure. However, light, moderate, and even severe complications may occur. A case of tissue necrosis at the upper lip after injection of highly cross‐linked hyaluronic acid together with the following salvage procedure is presented here. We discuss this complication with respect to relevant anatomy and physicochemical properties of the filler substance and review the recommendations given in literature for decreasing the likelihood of such an adverse event.